Дослідження гальмівного режиму тягового електропривода дизель-поїзда ДЕЛ-02 - Кулагін, Дмитро Олександрович (НТУ "ХПІ", 2010)
Two-region kvazivector control system traction’s electric drive of diesel engines-trains DEL-02, features of construction and works are discussed, witch use of an internal contour of regulation of an active component of a current in a link the operated rectifierindependent the pressure inverter.
Research of the brake mode of hauling electromechanic of diesel-train DEL-02
Keywords: електропривод частотно-керований; модель імітаційна; швидкість; струм електричний